The Announcement Effect of Junk Bond Issues: an Analysis of the 1976-1989 Period - Castillo R., Augusto (Estudios de Administración, 2001)
This paper analyzes the impact of corporate junk bond offering announcements on stock prices for a sample of 680 issues of below investment grade bonds, during the 1976-1989 period. The sample shows a -1.0% cumulative abnormal return (CAR) for a two day event window period, and the zero CAR hypothesis is rejected with 99% confidence. The cumulative abnormal returns are negative and significant for combined announcements of bond and equity issues (CAR of -2.10%), and for announcements of convertible bond issues (CAR of -1.24%). Announcements of issues of straight bonds (CAR of -0.24%) are not significantly different from zero. Differences in CARs are observed across subsamples formed on the basis of size of the issuer, relative size of the issue, rating of the issue, name of the underwriter, market value of the issuer, and year of issue, but these variables are not significant when used in cross sectional regressions. The only variables with some explanatory power in those regressions are the ones indicating type of the issue, recession periods, and the dummy used to identify announcements made in 1976 (the first year junk bond issues were allowed).